"My Surgical Success": Effect of a Digital Behavioral Pain Medicine Intervention on Time to Opioid Cessation After Breast Cancer Surgery—A Pilot Randomized Controlled Clinical Trial. Issue 11 (14th May 2019) - Darnall, Beth D; Ziadni, Maisa S; Krishnamurthy, Parthasarathy; Flood, Pamela; Heathcote, Lauren C; Mackey, Ian G; Taub, Chloe Jean; Wheeler, Amanda
Abstract: Objective: This study aims to assess the feasibility of digital perioperative behavioral pain medicine intervention in breast cancer surgery and evaluate its impact on pain catastrophizing, pain, and opioid cessation after surgery. Design and Setting: A randomized controlled clinical trial was conducted at Stanford University (Palo Alto, CA, USA) comparing a digital behavioral pain medicine intervention ("My Surgical Success" [MSS]) with digital general health education (HE). Participants: A convenience sample of 127 participants were randomized to treatment group. The analytic sample was 68 patients (N = 36 MSS, N = 32 HE). Main Outcomes: The primary outcome was feasibility and acceptability of a digital behavioral pain medicine intervention (80% threshold for acceptability items). Secondary outcomes were pain catastrophizing, past seven-day average pain intensity, and time to opioid cessation after surgery for patients who initiated opioid use. Results: The attrition rate for MSS intervention (44%) was notably higher than for HE controls (18%), but it was lower than typical attrition rates for e-health interventions (60–80%). Despite greater attrition for MSS, feasibility was demonstrated for the 56% of MSS engagers, and the 80% threshold for acceptability was met. We observed a floor effect for baseline pain catastrophizing, and no significant group differences were found for postsurgical pain catastrophizing or pain intensity. MSS was associated with 86% increased odds of opioid cessation within the 12-week study period relative to HE controls (hazard ratio = 1.86, 95% confidence interval = 1.12–3.10, P = 0.016). Conclusions: Fifty-six percent of patients assigned to MSS engaged with the online platform and reported high satisfaction. MSS was associated with significantly accelerated opioid cessation after surgery (five-day difference) with no difference in pain report relative to controls. Perioperative digital behavioral pain medicine may be a low-cost, accessible adjunct that could promote opioid cessation after breast cancer surgery.